Hierarchy of human needs in the main character of beauty is a wound by Eka Kurniawan - Siska, Siska (Universitas Ahmad Dahlan, 2021)
On this research, the researcher has aim to find out the main character Dewi Ayuâ€™s human needs and identify the most dominant needs. In this study, the researcher applied the psychological approach and theory of human needs. This research is a qualitative descriptive study. The writer uses a library research method to collect the data. It means that the writer visit the library and reads the novel then read several related books. The main data is novel beauty is a wound by Eka Kurniawan, while supporting data is obtained from books, articles, and the internet. The result of this study can be explained that the main character can not totally fulfill well, such as: (1) the physiological needs of the main character can be fulfilled well because she is from a wealthy family (2) the safety can not be fulfilled due to factors in that era (3) the love and belonging need can be fulfilled well because the main character has a beautiful appearance (4) the esteem needs can be fulfilled because she is a famous figure at that time (5) self-actualization needs also can be fulfilled well because the main character is a brave and is able to position herself very well. From the five hierarchy needs the most dominant need is safety needs.Â